Pengaruh Profitabilitas dan Kebijakan Dividen Terhadap Harga Saham Perusahaan Real Estate dan Property di Bursa Efek Indonesia - Janes Saputra Naibaho; Riska Franita (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to determine the effect of profitability and dividend policy on the stock price of Real Estate and Property Companies on the Indonesia Stock Exchange (IDX). This research uses quantitative research methods. This study uses secondary data obtained through the website www.idx.co.id. The population of this study was 75 companies which then eliminated a sample of 9 companies. The analysis technique used linear regression analysis and t test. The results of this study are as follows: 1) Based on the results of hypothesis testing, it is known that profitability affects stock prices with t-statistic test results of 2.20> 2.05 with a significance of 0.05, which is 0.03, this indicates that with a higher level of company profitability, the company's stock price will also be higher. 2) Based on the results of hypothesis testing, it is known that dividend policy affects stock prices with a t-statistic test result of 2.74> 2.05 with a significance of 0.05, namely 0.00, this indicates that the better the percentage of a company's dividend policy can affect the company's stock price, this is because many investors like companies that regularly distribute dividends.